La influencia de la actividad física extra laboral en la higiene postural del Personal Administrativo de la Unach Campus la Dolorosa, 2017-2018 - Ríos Tápia, María Soledad (2018)
In the present research entitled "The influence of extra-physical activity on postural hygiene of the administrative staff of the UNACH campus la dolorosa", whose objective was to determine the influence of extra-physical activity on the postural hygiene of administrative personnel of the UNACH, taking as a population the administrative staff of the National University of Chimborazo, with a total sample of 12 people, including 10 women and 2 men who participated in the intervention of bailoterapia. The present investigative work is of a quasi-experimental type of qualitative nature where a pre-post intervention evaluation was carried out using the Posturogram test, after concluding with the intervention of bailotherapy which lasted 8 weeks, the results of the program were analyzed. I dance therapy to see the influence of it on the postural hygiene of the administrative workers of the National University of Chimborazo, determining the relationship of the variables obtaining as a result a significant improvement in the deviation of the Achilles tendon and especially in the musculature of the abdomen; concluding with a total of 16 classes of bailoterapia realized to the university workers.